Combinational Effect of CYP3A5 and MDR-1 Polymorphisms on Tacrolimus Pharmacokinetics in Liver Transplant Patients. (2015)
ABSTRACT: Objectives: Previous studies have reported reduced tacrolimus dose-adjusted exposure in individuals expressing the CYP3A5*1 allele (reference single nucleotide polymorphism identification number 776746). However, results on patients from South America are scarce. The objective of this study was to investigate the influence of CYP3A5 and MDR1 allelic variants and their correlation on the pharmacokinetics of tacrolimus and a modified release formulation of tacrolimus in stable patients with liver transplant. Materials and methods: This was a prospective, single center, open-label study. Included patients were ≥ 18 years old and receiving a stable dose of tacrolimus for at least 6 months. Patients receiving stable treatment of twice daily tacrolimus were switched to a once-daily dose of modified release tacrolimus, on a milligram-to-milligram basis, with the modified release formulation administered for at least 4 weeks. Blood levels of tacrolimus were obtained before and 1 month after treatment was switched to the modified release formulation. Results: The frequency of the intron 3 allelic variant of the CYP3A5 isoform (G-to-A substitution at nucleotide 6986) in recipients was 16.6% and 25% in donors. Dose levels of tacrolimus and the modified formulation were significantly higher in donors and recipients who expressed CYP3A5 versus donors and recipients who did not express this allele. In addition, patients who received a liver from a donor expressing CYP3A5 had significantly lower trough concentrations of tacrolimus and the modified formulation. CYP3A5 expression in the donor liver affected tacrolimus (40.46%, P = .001) and modified formulation (37.56%, P = .001) variability. No association was found between the ABCB1 genotype and levels of tacrolimus or its modified formulation. Conclusions: Our data suggest that CYP3A5*1 in either the donor or recipient resulted in higher mean daily doses of tacrolimus or its modified formulation to achieve target drug exposure in liver transplant patients.